Online Gambling: A Tantalizing Game with Risks that Drain Fortunes and Futures - Igomu, Apolos; Muliyono, Andi; Bonggoibo, Alice Ance (Yayasan Sinergi Kawula Muda, 2024)
Online gambling has become an increasingly serious problem in Indonesia, affecting not only individuals but also social structures more broadly. This study aims to examine the prevalence and characteristics of online gambling among Indonesian adolescents and university students and find challenges and strategies in dealing with this problem. The data were analyzed using theme analysis, and the findings show that online gambling is a complex problem influenced by various factors, including ease of access, social influence, and financial incentives. This research shows that a comprehensive approach is needed in dealing with online gambling, involving the government, law enforcement, and civil society organizations. The findings suggest that public education and awareness campaigns are crucial in preventing online gambling, and law enforcement should be equipped with effective resources and technology to monitor and block online gambling activities. This research contributes to the existing literature by providing insights into the experiences and perceptions of Indonesian adolescents and university students who engage in online gambling. The findings also indicate the importance of a multi-faceted approach in dealing with online gambling, including the development of alternative recreational activities and the provision of counseling services for those affected by gambling addiction.